The Preparation and Formulation of Moringa oleifera Lam. Leaf Extract in Transdermal Patch - Sarumpaet, Ines Rianty; Sulastri, Titin; Suwitono, Marvel Reuben (Jurnal Biologi Tropis, 2025)
The anti-fibrotic, anti-inflammatory, and antimicrobial qualities of moringa leaf extracts, which are high in saponins, flavonoids, steroids, and phenols, can aid in tissue regeneration and wound healing. The aim of this study was to prepare and formulate a transdermal patch of Moringa oleifera Lam. leaf extract with hydroxypropyl methylcellulose (HPMC) and polyvinyl pyrrolidone (PVP) as the polymers. The study was aimed at investigating the effect of various concentrations of the extract (20%, 40%, and 80%) on the physical properties of the patch, including organoleptic properties, weight uniformity, thickness, folding endurance, pH, and water absorption. Extract was made by maceration with 96% ethanol, and patches were cast by the solvent casting method. Results showed that all formulations met the required pH range (6.62–6.68), folding endurance (>300 folds), and thickness (<1 mm). However, weight uniformity and moisture absorption exceeded desired optimum values and ranged between 17% to 23%. The 20% concentration of extract exhibited the maximum physical stability. This study highlights the potential of Moringa oleifera leaf extract in transdermal patch preparations, although it needs to be optimized to improve weight consistency and water absorption.